Meneladani Kepemimpinan Nabi Muhammad SAW dalam Prinsip Good Corporate Governance - Hesti Eka Tri Nur’Aini; Menik Puji Rahayu; Mohamad Djasuli (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
Muhammad SAW, the number one most influential man in the world. Muhammad was able to bring change in all aspects, ranging from religious, moral, and political matters through Islam. Good Corporate Governance is a system that functions as a company controller. Muhammad was a leader who succeeded in providing the welfare of the people fairly, not only Muslims but people from other religions. This leadership cannot be separated from the application of the principles of Good Corporate Governance to the Prophet. The method used in this research is descriptive qualitative by collecting data from books, scientific articles, and information from the internet. The results obtained from this study are the principles of Good Corporate Governance in line with the nature of the Prophet, namely Siddiq, Amanah, Tabligh, and Fathanah. This is the key to the success of the leadership of the Prophet Muhammad as the head of religion and government.